A REVIEW ON POWER QUALITY IMPROVEMENT FOR RENEWABLE ENERGY SYSTEM USING FACTS DEVICES (International Journal of Food and Nutritional Sciences, 2022)
This review examines power quality improvement in renewable energy systems using FlexibleAC Transmission Systems (FACTS) devices. With the increasing integration of renewablesources like wind and solar into the power grid, maintaining high power quality is essential.FACTS devices play a crucial role in mitigating issues such as voltage fluctuations, harmonics,and reactive power imbalance. This paper explores various FACTS technologies, theirapplications, and their effectiveness in enhancing power quality in renewable energy systems.The review highlights recent advancements, potential challenges, and future researchdirections in optimizing power quality through FACTS.